The changes in the profundal benthos during the extremely low water level in the deep lake Arakhley (Siberia) - Matafonov P.V. (BIO Web of Conferences)
Data on the impact of long-term water level fluctuations on benthic invertebrate communities of the deep lakes in Siberia are scarce due to the rarity of such events and the short history of observations. The studies of the dynamics of zoobenthos and the Chironomus anthracinus population in the central part of the profundal zone of the deep Lake Arakhley (Transbaikalia region, Russia) were carried out in December 2020-2023. The lake level was extremely low in 2020-2023. Zoobenthos biomass increased by 10.9 times from 6.6 g to 71.8 g/m2 from 2020 to 2023. The increase in zoobenthos abundance is due to increases in the number and biomass of oligochaetes Tubifex tubifex and chironomids Chironomus anthracinus. In December 2022, the Chironomus anthracinus population was dominated by second-instar larvae with a size of 8.7±0.08 mm, in 2023 - third-instar larvae with a size of 13.2±0.10 mm. The growth rate of Chironomus anthracinus corresponded to a three-year life cycle. Annual production of Chironomus anthracinus in 2022 was 16 g/m2, in 2023 – 22.8 g/m2. The results of the study revealed significant fluctuations in the structure, abundance and production of zoobenthos in the profundal zone of Lake Arakhley during the extremely low-water period.